Anhydrous Calcium Oxalate Polymorphism: A Combined Computational and Synchrotron X-ray Diffraction Study - Zhao, W.; Sharma, N.; Jones, F.; Raiteri, Paolo; Gale, Julian; Demichelis, Raffaella (American Chemical Society, 2016)
Four possible models for anhydrous calcium oxalate (COA) polymorphs have been investigated through ab initio quantum mechanical methods. Their structural properties, infrared and Raman spectra, and thermodynamic stability in the range of 0–800 K have been analyzed and compared. Along with the known β-COA structure, two models turn out to be possible candidates for the α- and γ-polymorphs that were observed during dehydration of weddellite (calcium oxalate dihydrate, COD) by Walter-Lévy and Laniepce ( C. R. Acad. Sci. Paris 1964, 259, 4685). While the calculated vibrational frequencies show that the four COA models correspond to minimum energy structures, β-COA is the thermodynamically favored phase over the range of temperatures examined in the present study. Despite the fact that computed vibrational spectra and X-ray diffraction (XRD) patterns of these polymorphs exhibit some different features, a definitive assignment of the structures based on computational results is not possible due to the lack of accurate experimental data. In an effort to improve comparative experimental data, the structural evolution of whewellite (calcium oxalate monohydrate, COM) has been probed using time-resolved synchrotron X-ray diffraction, in order to correlate the calculated structures to the observed structures. The evolution has been shown to go through at least four phases identified as COM, α-COA (corresponding to one of the models proposed by computation), β-COA, and CaCO3. The reactions are predominantly two-phase reactions, and at 140 °C evidence of three-phase coexistence has been noted between COM, α-COA, and β-COA. The time-resolved XRD data allow estimation of the kinetics of the reactions; these indicate second-order reactions between COM and α-COA and zeroth-order reactions between α-COA and β-COA.